Risk factors for horse falls in the cross-country phase of one day events - Cameron-Whytock, H.; Brigden, C. (DCA Report; Nr. 044, 2014)
Eventing is well recognised as a high risk sport, associated with higher levels of fatalities and serious injuries than other "dangerous" sports like motorsport and rugby. Understanding the most common causes and risk factors for cross country falls may help the industry implement preventative measures. The purpose of the study was to identify any significant risk factors associated with horse falls and to establish a spectator and rider view of the main concerns with safety in eventing. Data were collected from 2,002 horse and rider combinations in the Novice, Intermediate and Advanced levels of 37 randomly selected British Eventing one-day event competitions from 2003-2012. Binary logistic regression was used to examine the influence of competition level, horse age and gender, rider gender, position before cross country, month and year, and event on the probability of a horse fall. A self-administered online questionnaire was used to collect rider and spectator perspectives on eventing horse falls. The questions covered the participants` experiences of falls, either as a rider or spectator, and their opinions of the causes of horse falls and suggestions for safety improvements. Falls occurred in 4.78% of cross country starts (96 falls, number of starts=2,002). Position before the cross country was found to be the only significant predictor of horse falls (G=4.219; P<0.05). Competitors in a top three position before cross country were significantly more likely to have a horse fall than any other position (P<0.05). For example, riders in position 4-10 were 0.49 times less likely to have a fall than those in positions 1-3. Of questionnaire respondents (n=131: 61.83% riders, 29.77% spectators, 8.40% neither competitor nor spectator), 74.05% stated the main risk factor for a horse fall is rider error, followed closely by rider inexperience (64.88%). Speed was also identified as a key risk by respondents. Riders were significantly more likely to attribute horse falls to rider error than spectators (x²2=9.490, P<0.01). The study has identified that position before cross country is a significant risk factor associated with horse falls during competition. Riders in a more competitive position upon commencement of the cross country may have a tendency to take more risks or ride in a faster or more intense manner. Improved rider skill and understanding may be an approach to help reduce risks of falls in the future. It could also be considered whether placings should be concealed until after the cross country phase. LP: Horse and rider combinations in leading positions at the start of cross country are at greater risk of falls. Improved rider skill and understanding may help to reduce risks faced by horse and rider.